Causes and Management of Malabsorption, A Review: Life Sciences-Health - Baraa Emad M, Abuzinadah; Mazen Dhaher, Aljohani; Mesawa, Obai Taher; Sultan Abdullah A, Alharthi; Abeer Abdulrahman M, Alabi; Ahmed Saeed A, Saleh; Ziyad Zaid H, Almutawakkil; Mohsen, Ali Hasan; Albakr, Amirah Bakr; Al Antar, Awadh Mohammed; Alshahrani, Bashaiyer Mohammed; Abdullah H, Albanawi, Ayat; et al. (International Journal of Life Science and Pharma Research, 2022)
Maldigestion refers to poor nutritional digestion within the intestinal lumen or at the brush boundary, whereas malabsorption refers to decreased nutrient absorption at any point where nutrients are absorbed. Any flaw in the digestion/absorption process might cause malabsorption. Reduced absorption of certain nutrients, impaired GI motility (decreased peristalsis and stasis), altered bacterial flora, infection, or limited blood flow or weakened lymphatics are all possible causes for these problems. Protozoal infections of the small intestine are very frequent and may be linked to malabsorption. The majority of these infections are self-limiting. For the diagnosis of malabsorption, there is no gold standard. Additional tests should be done based on the clinical situation and the probable underlying condition. Nutritional assistance is provided by enteral or parenteral feeding, as well as screening for and treatment of vitamin and mineral deficiencies. In this article we will be looking at malabsorption causes and management.